Service of notice for determination in construction contracts - Wan Ibrahim, Wan Mohd. Izzuddin (2011)
Determination is a remedy provided under contract for a party to discharge his obligations upon breach by the other party. When the party to contract intends to determine a contract, he must let the other party knows his intention to do so. He is required to follow several procedures before he is said to determine the contract validly. Standard forms and bespoke construction contracts usually provide procedures for parties to contract to do so. Failure to adhere to the procedures may cause the termination invalid and the repercussions of such failure is severe and of serious consequences to the determining party. When one party exercises his intention to determine a contract, the other party often seeks to destroy his intention by claiming non compliance to procedural requirement for valid exercise of determination under the contract. One party argues that he has followed the required procedures for service of notice and the other party claims otherwise. This has led to numerous arguments and disputes between the parties often end with arbitrations or litigations. The arbitrators and courts are not helping either as decisions have not been consistent depending on how one construes the ambiguous words. The underlying matter is the interpretation adopted by arbitrators and courts in construing the ambiguous words. There are two commonest methods of interpretations used by arbitrators and courts in construing commercial contracts; by literal method or commonsense business method. Different interpretation method conveys different decisions. The question is which one would be the appropriate interpretation method for service of notice for determination in construction contract. Hence, this research intends to identify the appropriateness between the two methods. This research was carried out mainly through documentary analysis of law journals and law reports. Eleven law reports from various jurisdictions were used in this research. Result appears to indicate that commonsense business approach would be the appropriate interpretation method for service of notice for determination in construction contract. A concrete answer may not be found as the literal and commonsense business methods for interpretation are built on different nature and most of all how one interpret contracts depends on one’s conception of contracts. Absolutely, there is no easy answer to this. One thing is absolute is that employer or contractor considering to determine a contract in construction contracts must follow the procedures strictly.